L-Citrulline Supplementation Increases Plasma Nitric Oxide Levels and Reduces Arginase Activity in Patients With Type 2 Diabetes - Shatanawi, Alia; Momani, Munther S.; Al-Aqtash, Ruaa; Hamdan, Mohammad H; Gharaibeh, Munir N. (Frontiers in Pharmacology, 2020)
Type 2 diabetes mellitus (T2DM) is becoming a major contributor to cardiovascular disease. One of the early signs of T2DM associated cardiovascular events is the development of vascular dysfunction. This dysfunction has been implicated in increasing the morbidity and mortality of T2DM patients. One of the important characteristics of vascular dysfunction is the impaired ability of endothelial cells to produce nitric oxide (NO). Additionally, decreases in the availability of NO is also a major contributor of this pathology. NO is produced by the activity of endothelial NO synthase (eNOS) on its substrate, L-arginine. Reduced availability of L-arginine to eNOS has been implicated in vascular dysfunction in diabetes. Arginase, which metabolizes L-arginine to urea and ornithine, competes directly with NOS for L-arginine. Hence, increases in arginase activity can decrease arginine levels, reducing its availability to eNOS and decreasing NO production. Diabetes has been linked to elevated arginase and associated vascular endothelial dysfunction. We aimed to determine levels of plasma NO and arginase activity in (T2DM) patients and the effects of L-citrulline supplementation, a natural arginase inhibitor, on inhibiting arginase activity in these patients. Levels of arginase correlated with HbA1c levels in diabetic patients. Twenty-five patients received L-citrulline supplements (2000 mg/day) for 1 month. Arginase activity decreased by 21% in T2DM patients after taking L-citrulline supplements. Additionally, plasma NO levels increased by 38%. There was a modest improvement on H1Ac levels in these patients, though not statistically significant. The effect of L-citrulline on arginase activity was also studied in bovine aortic endothelial cells (BAECs) grown in high glucose (HG) conditions. HG (25mM, 72 hrs.) caused a 2-fold increase in arginase activity in BAECs and decreased NO production by 30%. L-citrulline (2.5mM) completely prevented the increase in arginase activity and restored NO production levels. These data indicate that L-citrulline can have therapeutic benefits in diabetic patients through increasing NO levels and thus maintaining vascular function possibly through an arginase inhibition related pathway.